2006
DOI: 10.1086/498982
|View full text |Cite
|
Sign up to set email alerts
|

Group BStreptococcusCrosses Human Epithelial Cells by a Paracellular Route

Abstract: Colonization of the colon and vagina is thought to be important in the pathogenesis of group B Streptococcus (GBS) infection. However, little is known about the strategies used by GBS to translocate through the epithelial barrier during the onset of disease. We used differentiated epithelial cells grown on transwell inserts as a model of the epithelial barrier. Bacterial translocation occurred without a detectable decrease in transepithelial resistance. Whereas acapsular GBS was better able to adhere to and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 28 publications
6
41
0
Order By: Relevance
“…In a previous study using electron microscopy, Soriani et al found that GBS strains use a paracellular route to cross cervical epithelial cells. The majority of GBS were found in the spaces between the cells, with very few passing through the cells themselves (30). Therefore, variation in invasive ability among GBS strains needs to be further tested using other assays that account for the paracellular route of invasion as well.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study using electron microscopy, Soriani et al found that GBS strains use a paracellular route to cross cervical epithelial cells. The majority of GBS were found in the spaces between the cells, with very few passing through the cells themselves (30). Therefore, variation in invasive ability among GBS strains needs to be further tested using other assays that account for the paracellular route of invasion as well.…”
Section: Discussionmentioning
confidence: 99%
“…Plasminogen recruitment has been demonstrated to contribute to bacterial virulence through mediating adhesion to host cells (41,60,61). In addition, activation of the recruited plasminogen to plasmin has been demonstrated to play a role in the breakdown of extracellular matrix proteins (41)(42)(43)(44) and may contribute to GBS paracellular invasion (62). Initial experiments demonstrated that GBS encodes several plasminogen binding proteins, one of which was identified as GAPDH (43).…”
Section: Discussionmentioning
confidence: 99%
“…There is a distinction between pathogens that utilize a transcellular route to cross epithelial cell monolayers (19) and bacteria that cross by a paracellular route after destruction of cells of the layer or disruption of tight junctions (1,10,18,34,35,40,55,59,68). There is conflicting evidence about the route that the meningococcus takes to traverse the epithelial cell barrier in the nasopharynx.…”
Section: Discussionmentioning
confidence: 99%